Enhancing the Prospects of Growth and Trade of the Kyrgyz Republic - World Bank (Washington, DC, 2013)
The Kyrgyz Republic has made major strides in the past decade in its transition to a market-based economy. Its trade and investment policies are arguably the most liberal among the member countries of the Commonwealth of Independent States. This report is aimed at assisting authorities fashioning this agenda by focusing on three key challenges: Identifying strategic options to strengthen prospects for medium- and long-term growth and poverty reduction; Assessing ways of leveraging domestic trade policy reforms and existing regional and multilateral trade agreements for further regional and global integration; and Identifying key areas where greater efforts are necessary to facilitate improvements in enterprise capability and productivity.